Analisis Fenomena Culture Shock dan Proses Adaptasi Mahasiswa Rantau Pasca Pandemi Covid-19 - Alquzairi, Tengku Muhammad Hilal; Rozaq, Miftahul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The COVID-19 pandemic has brought significant changes to daily life, including in the world of education. Overseas students, especially the class of 2020 at Telkom University, experience unique challenges in adapting to a new environment amid restrictions caused by the pandemic. This study aims to analyze the phenomenon of culture shock and the adaptation process carried out by overseas students at Telkom University, Bandung. Using a qualitative approach with phenomenological methods, this study explores the personal experiences of overseas students from various provinces in Indonesia, especially those from Medan. The results showed that students experienced various levels of culture shock influenced by changes in learning methods from face-to-face to online, limited social interaction, and regional cultural differences. The adaptation process involved strategies such as blending into the new environment, using technology in communication, and adjusting to new learning methods. This research provides insight into the importance of academic and social support for overseas students in dealing with culture shock and adaptation in the post-COVID-19 pandemic higher education environment